Complex, intelligent, and software intensive systems : proceedings of the 12th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2018) /: proceedings of the 12th International Conference on Complex, Intelligent, and Software Intensive Systems (CISIS-2018). ([2019]) - Unknown
No abstract available